GDNF and NT-4 protect midbrain dopaminergic neurons from toxic damage by iron and nitric oxide - Lingor, Paul; Unsicker, Klaus; Krieglstein, Kerstin (Experimental neurology, 2002)
Free radical formation is considered to be a major cause of dopaminergic (DAergic) cell death in the substantia nigra leading to Parkinson's disease (PD). In this study we employed several radical donors including iron and sodium nitroprusside to induce toxic effects on DAergic neurons cultured from the embryonic rat midbrain floor. Overall cell survival was assessed by assaying LDH, and DAergic neuron survival was monitored by counting tyrosine hydroxylase-positive cells. Our data suggest that the DAergic neuron population is about fourfold more susceptible to free-radical-mediated damage than the total population of midbrain neurons. Application of the neurotrophic factors GDNF and NT-4, for which DAergic neurons have specific receptors, prior to toxin administration protected these neurons from toxin-mediated death, which, fully or in part, occurs under the signs of apoptosis. These findings underscore the importance of GDNF and NT-4 in designing future therapeutical concepts for PD.
Gesehen am 24.11.2016